Avaliação da distribuição espacial e dos aspectos epidemiológicos dos casos notificados de tuberculose na região do Pontal do Paranapanema - BORTOLUCI, Anne Beatriz (2018)
Tuberculosis (TB) is a chronic infectious disease, widely distributed worldwide, and has long affected humanity, and still represents a serious public health problem. In 2015, the estimated global incidence for tuberculosis was 144 cases per 100,000 inhabitants, totaling around 10.4 million cases worldwide. Pontal Paranapanema is a region comprising 32 municipalities in the state of São Paulo, located in the extreme west of the state, southeast region of Brazil. This region has government programs that stimulate family farming, houses many rural settlements and settlements, and additionally covers the largest number of prisons in the country. Considering the socioeconomic, cultural and environmental characteristics of the region, the present study aims to evaluate the spatial distribution of reported cases of tuberculosis in the region of Pontal Paranapanema between 2007 and 2015, as well as to identify endemic regions and related factors. The research was carried out in 4 stages: 1) data collection on TB cases and characteristics of individuals reported from the National System of Aggravations and Notification (SINAN); 2) statistical analyzes, from the Prais-Winsten regression model, Durbin-Watson test and Pearson correlation; 3) production of thematic maps in Geographic Information System software; and 4) identification of endemic outbreaks of TB in the Pontal Paranapanema. 2221 cases of TB were reported in all clinical forms in region, between 2007 and 2015. Most of reported cases were white male individuals aged between 20 and 39 years, with many illiterates. In addition, the cure rate and the percentage of treatment abandonment did not reach goals established by the World Health Organization. It is concluded that the spatial distribution of tuberculosis in the 32 municipalities studied is not homogeneous, revealing it as an endemic problem in the region of Pontal Paranapanema, concentrating on four municipalities. The trend analysis of the disease was not linear. To achieve WHO goals, better integration between managers and professionals at the federal, state and municipal levels is required.